Guidelines for exploiting natural resource wealth - Van der Ploeg, R (University of Oxford, 2013)
The principles of how best to manage the various components of national wealth are outlined, where the permanent income hypothesis, the Hotelling rule and the Hartwick rule play a prominent role. As far as managing natural resource wealth is concerned, a case is made to use an intergenerational sovereign wealth fund to smooth consumption across generations, a liquidity fund for the precautionary buffers to deal with commodity price volatility, and an investment fund to park part of the windfall until the country is ready to absorb extra spending on domestic investment. Capital scarcity implies that a positive part of the windfall should be spent on domestic investment. The conclusions highlight the political economy problems that will have to be tackled with these normative proposals for managing wealth.